Eight‐port orthogonally dual‐polarised MIMO antennas using loop structures for 5G smartphone. Issue 12 (1st September 2017) - Li, Ming‐Yang; Xu, Zi‐Qiang; Ban, Yong‐Ling; Sim, Chow‐Yen‐Desmond; Yu, Zhe‐Feng
Abstract : An eight‐port antenna array designed for future 5G 2.6 GHz band (2550–2650 MHz) for multi‐input multi‐output (MIMO) in the smartphone applications is presented. In order to enhance the port isolation and reduce correlation between antennas, square loop radiating strip with orthogonal polarisation is employed. The proposed antenna array is composed of four pairs of uniform antenna elements that are symmetrically placed at the four corners of the main board, and each antenna pair includes a communal square loop and two independently coupled feeding strips. By exciting the square loop from the two feeding strips, respectively, two orthogonally polarised waves are generated. Thus, four horizontally polarised and four vertically polarised antennas are achieved in total. Due to this feature, coupling between antenna pairs is reduced and the MIMO performances are enhanced. A prototype of the proposed antenna array was fabricated, and the experimental results show good impedance matching and acceptable isolation measured across the bands of interest. The MIMO performances such as envelope correlation coefficient, mean effective gain, multiplexing efficiency and channel capacity are also calculated. Besides, simulations of the antenna shifted to 3.5 GHz are also performed. The consistent performances indicate that the proposed structure has good scalability and is promising for future 5G smartphone applications.